A proposed software for controlling operating system-dependent functionality - Abdulameer Alazawi, Sundos; Mahmood Hussien, Nadia; Makki Mohialden, Yasmin; Mohammed, Mostafa Abdulghafoor (Institute of Advanced Engineering and Science, 2023)
When the operating system environment temperature rises above safety, the CPU may become unresponsive or even malfunction. To address this problem, to achieve this goal a two-part system was designed. The first, consists of a controlled sensor that constantly monitors the room environment temperature and alerts the user if it rises above acceptable levels for computer use. The second part adopts a Python that uses the OS module, which provides a portable interface for OS-dependent tasks and shuts down the device to prevent it from behaving unexpectedly. A series of experiments at different temperatures demonstrated the ability of the device to alert the user.